Olfactory sex preferences in six Estrildid Finch species - Krause, E. Tobias; Paul, Madeleine; Krüger, Oliver; Caspers, Barbara A. (Frontiers in Ecology and Evolution, 2023)
Avian courtship behaviour is essential to attract potential mating partners. Courtship behaviours can involve displays of different sensory modes. Sex discrimination is a crucial step and in many bird species, sexes differ in acoustic and visual traits, allowing sex discrimination. It has been shown only recently that in some species of Estrildid Finches, chemical cues are involved in social communication. Here, we investigated whether olfaction also plays a role in sex discrimination in Estrildid Finches. Investigating olfactory sex preferences as an indicator behaviour in six different Estrildid Finch species, we aimed to understand whether sex- and/or species-specific differences in olfactory preferences exists and whether olfactory sex preferences correspond to species-specific differences in sex-specific acoustic and visual displays, e.g. singing, plumage dimorphisms and courtship dance. Olfactory sex preferences were tested in a Y-Maze test. We found differences in scent preferences among the different species of Estrildid Finches. We discussed the behavioural pattern with respect to other species-specific traits. And their potential implications in a broader mate choice context.